PENGARUH PEMBERIAN EKSTRAK BIJI PEPAYA (Carica Papaya L.) DAN EKSTRAK DAUN MIMBA (Azadirachta Indica A. Juss)DAN CAMPURAN EKSTRAK BIJI PEPAYA DAN EKSTRAK DAUN MIMBA TERHADAP KUALITAS SPERMATZOA MENCIT (Mus Musculus) - Hasanah, Waqiatul; M.Kes, Dr.Dra Sukarjati (LPPM Universitas PGRI Adi Buana Surabaya, 2016)
Seeds of papaya (Carica Papaya L.) and leaves of neem (Azadirachta indica A. Juss) is an herbal plant. In papaya seeds contain of alkaloids, Papain, tannins, saponins, Triterpenoid, Flavonoids. On the part of Neem leaves contain tannins, Saponins, Triterpenoid, Flavonoids. These compounds are compounds that function as antifertility for men. This has led the authors to conduct research on the effect of seed extract of papaya (Carica Papaya L.) and the leaf extract of neem (Azadirachta indica A. Juss) on the quality of spermatozoa of mice (Mus muscullus). The Samples were as many as 21 mice sperm tails with a weight of 20-30 grams, 2-3 months old. Mice divided in the 3 groups, each group was divided 7 treatments. The treatment given is control, papaya seed extract, neem leaf extract and a combination of both papaya seed extract and neem leaves with a concentration of 0 mg/kg bw, 50 mg/kg bw and 100 mg/kg bw 50:50 mg/kg bw, 100: 100 mg/kg bw. 35 days for extract. On day 37 mice in surgery for cauda epididymis were taken for observation of the quality of spermatozoa of mice. This study was an experimental study using randomized block design (RAK). The Observation of the quality of spermatozoa includes motility, viability, and morphology of spermatozoa concentration by using a microscope. Data were analyzed by analysis of variance (ANOVA) One Way. The results of this study showed that there is effect of papaya seed extract and neem leaf extract and a combination of both papaya seed extract and neem leaf on motility (P <0.05), viability (P <0.05), morphology (P <0.05) and sperm concentration (P <0.05). The results of this study concluded that neem leaf extract at a concentration of 100 mg/kg bw is the optimal treatment in reducing the viability of spermatozoa of mice. Extracts combination of papaya seeds and leaves of neem with a concentration of 100 mg/kg bw is the optimal treatment in reducing the motility and concentration of spermatozoa of mice. Papaya seed extract at a concentration of 100 mg/kg bw optimal in reducing the number of normal sperm in mice. Keywords: papaya seed extract (Carica Papaya L.), Neem Leaf Extract (Azadiracta indica A. Juss), the quality of spermatozoa of mice (Mus muscullus)